Knowledge, Attitudes, and Practices of Mothers of Preschool Children About Oral Health in Qatar: A Cross-Sectional Survey - Asmaa Alkhtib; Abdul Morawala (MDPI AG, 2018)
Health-related behaviors are influenced by knowledge and awareness, with oral health being no exception. It is well-known that oral diseases are influenced by social determinants. There is an association between the oral health knowledge of mothers and the status of their children's oral health. In Qatar, the knowledge and practices of oral health in preschool children have not been previously reported. The aim of this study was to assess the knowledge, attitude, and related practices of mothers of preschool children about oral health in Qatar. A total of 400 questionnaires were distributed by the principals of kindergarten to mothers of children attending 16 government kindergartens in Qatar. The questionnaire included 38 close-ended questions grouped into nine categories, addressing different aspects of knowledge and practices related to early childhood oral health. The questionnaire was constructed in English, before being translated into Arabic, which is the local language in Qatar. The questionnaire instrument was pre-tested on mothers with demographic characteristics matching the main population. These participants were not included in the main study. The questionnaire study was associated with a clinical epidemiological study to assess dental caries and enamel defects of the sampled children. The dmft caries index (decayed, missing and filled teeth) was used for that purpose according to the World Health Organization criteria. For the questionnaire administered to mothers with clinical survey variables, a binary logistic regression analysis was performed to determine the associations between the measures of oral health status (dmft, Dental index) and mothers' oral health knowledge and practices. A total of 48% mothers thought that children should have their teeth brushed from the age of three years and 42% chose younger than two years as a starting age for brushing. More than half (54%) of the mothers thought that children should not have their teeth flossed. In general, no significant statistical association was found between dmft and any other variables, except for whether or not the child had visited the dentist. Logistic regression analyses were performed to determine the association between the measures of oral health status (dmft, DI) and mothers' oral health knowledge and practices. After controlling for the other independent variables included in this model, the test of the model was not statistically significant, which indicated that none of the variables represent a significant risk for occurrence of caries. The only exception was whether or not the child had visited the dentist (odds ratio = 2.51, 95% confidence interval 1.091-5.774). Despite the existence of good knowledge of oral health care, there were deficiencies in the oral health care provided to children. This may reflect that seeking dental care is either not very important or it is challenging to obtain access to a child-friendly dentist in the public health system in Qatar. The results of this study suggest that there is a need for an oral health promotion program to fill the gaps in knowledge for mothers regarding oral health care for young children.